A lower profile base station antenna: With dual‐polarization and dual‐band for sub‐6 GHz application. Issue 6 (25th March 2021) - Qi, Junwu; Qiu, Yuanzhong; Gao, Bin; Liu, Ruipeng; Cui, Wenjie; Fan, Chao; Wang, Mengjun; Zheng, Hongxing; Li, Erping
Abstract: A compact dual‐band antenna is designed in this paper, which consists of a pair of lower band (LB) element and four higher band (HB) elements operating at 0.69 to 0.96 GHz and 3.3 to 3.6 GHz, respectively. Four HB elements are put between the adjacent dipole arms of LB element. All of elements are at the same height, and having their own reflector. A designed dual‐band dual‐polarized antenna at high frequency ratio will be fulfilled without added any other structure. The fabricated antenna sample has been measured, results show that the average gains of LB and HB elements are 8.48 dBi and 8.44 dBi and the half power beam widths are 69.1° ± 9° and 60.7° ± 8.5°, respectively. Moreover, dual‐polarized property of both LB and HB is checked. The cross‐polarization discrimination values are greater than 15 dB. The proposed antenna is implemented the coverage of two bands with high frequency ratio with a simple structure, and the antenna with both low profile and high gain characteristics. All of the results demonstrate that the antenna radiation boasts its favorable performance and can be a good candidate in 5G mobile communication system for sub‐6 GHz base stations.